Service quality comparison between chain and standalone hotels (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Chain hotels and independent hotels are now competing more fiercely than ever before due to the development and diversity of the hospitality sector. In recent years, service quality has been seen as a key factor in determining customer happiness, loyalty, and overall company success. The purpose of this research is to evaluate the relative merits of chain hotels and independently owned establishments in terms of service quality along important aspects like responsiveness, empathy, assurance, reliability, and tangibles. The service at different sites of the same chain hotel is usually rather consistent because of the chain's standardised operations, consistent branding, and well-trained employees. The emphasis on cultural distinctiveness, personalisation, and flexibility at standalone hotels, on the other hand, may increase client happiness but isn't always consistent. Utilising primary and secondary data, including surveys, customer feedback, and service quality evaluation methods like SERVQUAL, the research takes a comparative analytical approach. According to the results, chain hotels are great at infrastructure, professionalism, and dependability, while independent hotels are far better at providing individual attention and engaging with guests. But there are holes in both industries, especially when it comes to keeping service consistent and meeting customers' ever-changing expectations. The research found that the hospitality industry might benefit greatly from a hybrid strategy that combined the measured efficiency of chain hotels with the individual attention of independent businesses. Hotel management may use the findings of this study to boost customer happiness and gain a competitive edge by better comprehending the dynamics of service quality.